The Influence of Corporate Sustainability Performance (CSP) on Profitability with Liquidity and Leverage as Moderating Variables in LQ45 Index Companies on the Indonesia Stock Exchange (IDX) - Radhiyatul Bilqis; Yumna, Aimatul (Financial Management Studies, 2024)
This study aims to analyse the effect of corporate sustainability performance (CSP) on profitability with liquidity and leverage as moderating variables in LQ45 companies listed on the Indonesia Stock Exchange (IDX). This research is a causative research. The population in this study were all LQ45 indexed companies listed on the IDX for the 2019-2023 period. The sampling technique in this study was purposive sampling so that 18 companies were selected. The type of data used is secondary data obtained from the IDX website www.idx.co.id and the company's official website. The analysis method used is panel data regression analysis using STATA version 14.2. The results of this study indicate (1) corporate sustainability performance (CSP) has a positive and significant effect on profitability, (2) liquidity as a moderating variable can strengthen the relationship between corporate sustainability performance (CSP) and company profitability, (3) leverage as a moderating variable can weaken the relationship between corporate sustainability performance (CSP) and company profitability.